Value of preoperative arteriography in the definition of patent arterial axes in the leg and foot - Rudnitzky, Omar; Davezac, Víctor; Blanco, Raúl; Gordillo, Felipe (Cirugía del Uruguay, 1993)
Taking into account that in rescue surgery of the lower limbs is not uncommon to use vascular axis of leg or foot as by-pass receptors, the authors analysed the results of 59 aortographys carried out by translumbar puncture and 38 arteriographys by femoral puncture in arder to define permeable arterial axis of leg and foot.